Aplikasi Pembelajaran Anatomi Tubuh Manusia berbasis Android untuk Siswa Sekolah Dasar - Dian Nazelliana (Teknik Informatika Universitas Pamulang, 2020)
SDN Beji Timur 3 is an elementary school in the Depok area. The delivery of cognitive learning material in this school using conventional methods has an effect on the effectiveness of student learning at school. Learning activities have two important elements in the form of teaching methods and learning media and the two are interrelated. The process of selecting teaching methods is also adapted to the learning media. Several aspects need to be considered in relation to the objectives of learning activities, types of tasks. Another aspect is the response of students during learning activities including student characteristics. Learning media has the main function as a tool for educators to teach that is influenced by climate, conditions, and the environment. Efforts to improve effective learning methods to accelerate the learning process so that learning materials are delivered interestingly at the right time. This study answers this learning problem by creating an Android-based learning media application to explain material about the introduction of human anatomy.